The Water & Conflict Podcast, with CGIAR - Episode 3 - International Water Management Institute (International Water Management Institute, 2024)
In this last episode, hosts Christine Akume David and Bunmi Afolabi invited IWMI’s Adebayo Oke, Regional Researcher for agricultural water solutions, Rahab Jasini, Adamawa State Teacher, and John T. Gadzama, Adamawa State Internally Displaced Persons (IDP) Leader back into the studio.